Análisis de la recaudación tributaria del impuesto a la renta en el Ecuador - Loor Santana, Frank Nicolas (2023)
The following study highlighted the importance of income tax collection in Ecuador and tax revenues as a source of financing for the country and its role in the provision of public goods and services. It mentions that taxes are mandatory contributions that allow the State to provide services to citizens. It also highlights the social problems in Ecuador, such as inequality and poverty, and how fiscal policy can be used to address these challenges. It mentions that distrust in the quality of spending and investment has led to an increase in tax evasion. The analysis focuses on income tax, describing its definition and the returns for individuals and corporations. The taxable bases and deductions for calculating the tax payable are detailed. In addition, mention is made of the General State Budget and the importance of tax revenues to finance public services. The text concludes by highlighting the relevance of the Income Tax for the general collection and analyzes the variations in the collection during the period 2017-2021. Recommendations are put forward to promote tax culture, encourage investment and carry out tax reforms to address the effects of the pandemic and promote economic growth in Ecuador.